The genome of the sapphire damselfish Chrysiptera cyanea: a new resource to support further investigation of the evolution of Pomacentrids - Emma Gairin; Saori Miura; Hiroki Takamiyagi; Marcela Herrera; Vincent Laudet (GigaByte)
The number of high-quality genomes is rapidly increasing across taxa. However, it remains limited for coral reef fish of the Pomacentrid family, with most research focused on anemonefish. Here, we present the first assembly for a Pomacentrid of the genus Chrysiptera. Using PacBio long-read sequencing with 94.5× coverage, the genome of the Sapphire Devil, Chrysiptera cyanea, was assembled and annotated. The final assembly comprises 896 Mb pairs across 91 contigs, with a BUSCO completeness of 97.6%, and 28,173 genes. Comparative analyses with chromosome-scale assemblies of related species identified contig-chromosome correspondences. This genome will be useful as a comparison to study specific adaptations linked to the symbiotic life of closely related anemonefish. Furthermore, C. cyanea is found in most tropical coastal areas of the Indo-West Pacific and could become a model for environmental monitoring. This work will expand coral reef research efforts, highlighting the power of long-read assemblies to retrieve high quality genomes.